A floating collagen matrix triggers ring formation and stemness characteristics in human colorectal cancer organoids - Wimmers, Daniel; Hübner, Kerstin; Dale, Trevor; Papargyriou, Aristeidis; Reichert, Maximilian; Hartmann, Arndt; Schneider-Stock, Regine (Pathology Research and Practice, 2025)
Intestinal organoids reflect the 3D structure and function of their original tissues. Organoid are typically cultured in Matrigel, an extracellular matrix (ECM) mimicking the basement membrane, which is suitable for epithelial cells but does not accurately mimic the tumour microenvironment of colorectal cancer (CRC). The ECM and particularly collagen type I is crucial for CRC progression and invasiveness. Given that efforts to examine CRC organoid invasion in a more physiologically relevant ECM have been limited, we used a floating collagen type I matrix (FC) to study organoid invasion in three patient-derived CRC organoid lines. In FC gel, organoids contract, align, and fuse into macroscopic ring structures, initiating minor branch formation and invasion fronts, phenomena unique for the collagen ECM and otherwise not observed in Matrigel-grown CRC organoids. In contrast to Matrigel, FC organoids showed basal extrusion with improper actin localization, but without change in the organoid polarity. Moreover, small clusters of vital invading cells were observed. Gene expression analysis revealed that the organoids cultured in a FC matrix presented more epithelial and stem cell-like characteristics. This novel technique of cultivating CRC organoids in a FC matrix represents an in-vitro model for studying cancer organization and matrix remodelling with increased organoid stemness potential.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Collagen I; Invasiveness; Matrigel; Ring structures; Stemness; TROP2